Examining the rate of pregnancy with assisted reproductive technology and the outcome of pregnancy in women referring to the infertility center of Ardabil city - Jalilvand, Faranak; Farzipour, Shahla; Amani, Firouz; Biriya, Atousa (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Assisted reproductive technology (ART), including in vitro fertilization (IVF) and microinjection or intracytoplasmic sperm injection (ICSI) and intrauterine sperm injection (IUI) has been widely used to solve the problem of human infertility and has brought many benefits to millions of women and men. The husband is dealing with infertility disorders. The aim of this study was to determine the rate of pregnancy with ART and the outcome of pregnancy in women. Methods: In this descriptive-cross-sectional retrospective study 380 women who visited the infertility center of Ardabil city Alavi hospital from the beginning of October 2017 to the end of September 2019 to get pregnant with assisted reproductive methods. Data were collected by a checklist and then were analyzed by statistical methods in statistical package for the social sciences (SPSS) version 24. Results: The most important cause of infertility was attributed to ovarian causes with 36.5% and then male causes with 27.8%. In total, 82 people (22.6%) got pregnant out of 380 people referred for infertility treatment. Among these 82 people, 51.2% of healthy and full-term babies and 22.0% of healthy and pre-term babies were born. Also, 26.8% had no birth due to various reasons. Conclusions: The results showed that the results of treatment with pregnancy methods in Ardabil are acceptable. The IUI method had the highest success rate in terms of pregnancy and the IVF method had the highest success rate in terms of the birth of a healthy baby.